Drug resistance towards etoposide and cisplatin in human melanoma cells is associated with drug-dependent apoptosis deficiency - Röckmann, Heike; Schadendorf, Dirk (The journal of investigative dermatology, 2015)
Anticancer drugs kill susceptible cells through induction of apoptosis. Alterations of apoptotic pathways in drug-resistant tumor cells leading to apoptosis deficiency might represent a potent mechanism conferring drug resistance. We have assessed the effect of etoposide and cisplatin on the apoptotic pathways of the drug-sensitive human melanoma cell line MeWo as well as its etoposide- and cisplatin-resistant sublines (MeWoEto01, MeWoEto1, and MeWoCis01, MeWoCis1). Etoposide and cisplatin induced apoptosis in drug-sensitive MeWo cells as indicated by dose-dependent (i) cytochrome c release, (ii) caspase activation, (iii) DNA fragmentation, and (iv) cleavage of poly(ADP-ribose)polymerase. In contrast, whereas low etoposide-resistant cells (MeWoEto01) demonstrated reduced but detectable apoptotic activities, highly etoposide-resistant cells (MeWoEto1) did not exhibit any of the apoptotic events observed in etoposide-induced cell death downstream of a strongly reduced cytochrome c release. Highly cisplatin-resistant cells (MeWoCis1), however, demonstrated a reduced caspase 9 activity and cytochrome c release but the extent of effector caspase activation as well as DNA fragmentation was comparable to that of sensitive MeWo cells at equitoxic concentrations. In addition, poly(ADP-ribose)polymerase cleavage was strongly reduced in highly cisplatin-resistant sublines. Taken together, sensitive and drug-resistant MeWo cells utilized different apoptotic pathways upon drug exposure in a drug-dependent fashion and apoptosis deficiency was strongly associated with the drug-resistant phenotype.